Territórios, classes e experiências: as dobraduras do espaço e tempo nas trajetórias de vida - Diniz, Rodrigo Aparecido (2021)
This thesis aims to understand the mediation of class experiences in the construction of territories, taking as an empirical reference the reality of Anhanguera district, a peripheral area located at the end of northern zone of Sao Paulo city. It has the objectives to reflect the links between the categories of space and time in the production and reproduction process of the territories; to study the relations between territories, the incidences of the new flows in the capitalist production mode upon spaces and ways of life. To analyze the constitutive processes in the experiences of the class layers who live from work in the context of the subjects’ lives in the construction of territorial spaces. The research recognizes the life trajectories of four women who are interlocutors and participants in the study, evidencing the hypothesis that it is possible to understand the class experiences as constituents of territories and territorialities in the urban scenario of cities, as it is in the plot of the daily life of the places that the material and spiritual life of the classes are manifested and constitute ways of life and sociability. The research method moves based on historical-dialectical materialism, which seeks to understand the mediations inherent to the historical process, its contradictions, in the critical dialogue based on successive approximations between singularity, particularity and totality in relation to class experiences, territories and process of production and reproduction of life in urban peripheries. The chosen research methodology is oral history, which allows the recognition of oral sources as particular elements of the participating subjects’ narratives, but based on the theoretical-methodological, ethical-political and sociological rigor, they are saturated with mediations that show and relate to the broadest structures and social processes. The results of the research show that the experiences of the class that lives from work are traced within the scope of practices and social accumulations inherent to the peripheral and territorial way of life with regard to the sociability of living, living and building their territories amid struggles and economic precariousness, social, political and health issues. They also point out the potentials in relation to solidarity, bonds and belongings between residents and their territories of life. The relations of construction and reconstruction of territories are intended in the folds between classes relation, ethnic-racial and gender relations that draw experiences with historical roughness of exploitation, violence and oppression that interrelate and modulate the sociability, the objective and subjective forms of the ways of life in the peripheries. The research is also attentive to the contradictions inherent to the State's mediation practices and also to organized crime in the poor territories of the city, which are shown in violent institutions, which have repercussions and impacts on the daily lives and ways of life of the residents of the peripheral territories, showing the political-cultural transformations in effervescence in the peripheral territories